2018
DOI: 10.1002/fsn3.765
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Talinum triangulare leaf flavonoid extract on streptozotocin‐induced hyperglycemia and associated complications in rats

Abstract: Talinum triangulare leaf flavonoid extract (TTFE) was evaluated for its effects on streptozotocin‐hyperglycemia and associated complications especially as it relates to dyslipidemia, lipid peroxidation, and renal dysfunction in rats. Two normoglycemic rat groups designated: control (administered distilled water) and control + TTFE (administered 10 mg/kg b.w. TTFE) and two streptozotocin‐induced (STZ) diabetic rat groups designated: STZ‐control (administered distilled water) and STZ + TTFE (administered 10 mg/k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(70 reference statements)
1
5
0
1
Order By: Relevance
“…It was also observed that treatment with extract of T. triangulare for 21 days significantly improved serum insulin level in STZ-induced diabetic rats compared to the untreated diabetic group. Authors equally observed improved kidney function, lipid profile and antioxidant status following the administration of flavonoid fraction from the extract of T. triangulare (27). Also, the inhibitory activity of T. triangulare flavonoids on alpha-amylase activity may have played a role in the reduction of carbohydrate hydrolysis and absorption in the intestine, culminating in the reduction of serum glucose levels in this study (27,61).…”
Section: Antidiabetic and Hypoglycaemic Activity Of T Triangularesupporting
confidence: 53%
See 3 more Smart Citations
“…It was also observed that treatment with extract of T. triangulare for 21 days significantly improved serum insulin level in STZ-induced diabetic rats compared to the untreated diabetic group. Authors equally observed improved kidney function, lipid profile and antioxidant status following the administration of flavonoid fraction from the extract of T. triangulare (27). Also, the inhibitory activity of T. triangulare flavonoids on alpha-amylase activity may have played a role in the reduction of carbohydrate hydrolysis and absorption in the intestine, culminating in the reduction of serum glucose levels in this study (27,61).…”
Section: Antidiabetic and Hypoglycaemic Activity Of T Triangularesupporting
confidence: 53%
“…It is cultivated in Nigeria and Cameroon by seedling and cuttings. There are approximately 500 species of the genus Talinum globally (27). T. triangulare is sensitive to cold conditions and its roots will rot when water is logging in the soil.…”
Section: Distribution Cultivation and Harvesting Of T Triangularementioning
confidence: 99%
See 2 more Smart Citations
“…Given its numerous health bene ts, avocado peel waste is considered a promising, low cost biomass for salvaging phenolic compounds from agro-wastes. Hence, the exploitation of avocado peel waste will go a long way in adding value to avocado processing industry as well served as a veritable strategy for reducing the environmental impacts of avocado wastes 12 . The potential inhibition of α-amylase by certain food and plant extracts was reported recently.…”
Section: Introductionmentioning
confidence: 99%